ABO and Rh D Blood Groups in Plasmodium falciparum Infected Subjects at Aminu Kano Teaching Hospital, Kano – Nigeria - Danladi, S.B., Garba, N., Buhari, D.U. (Sokoto Journal of Medical Laboratory Science)
The interplay between malaria parasites and blood group antigens remains a fascinating subject with potential to contribute to the development of new interventions to reduce the global burden of malaria. Elucidation of the ABO and Rh D blood group antigens status and infection with Plasmodium falciparum can bring about understanding of the differences noted in the ABO blood group variation in malaria endemic areas. The aim of this study was to assess the distribution of ABO and Rh D blood groups in relation to P. falciparum malaria infection in subjects infected with malaria receiving medical care at Aminu Kano Teaching Hospital, Kano. A total of 388 plasmodium falciparum infected subjects were recruited for this study. The ABO and Rh D blood groups of all participants were determined using standard tube technique while P. falciparum infection and the parasitaemia levels were also determined microscopically by thin and thick blood films, respectively. The blood groups were O Rh D+ 190 (48.97%), blood group A Rh D+ 95 (24.48%), blood group B Rh D+ 83 (21.39%), blood group AB+ 14(3.61%), blood group O Rh D- 3 (0.77%), blood group A RhD- 1 (0.26%), blood group B Rh D- 2 (0.52%), and blood group AB Rh D- 0 (0%). The result of this research shows that the ABO blood group O is the most common, followed by group A, group B is less common and group AB is the least common. We concluded that blood group O offers a survival advantage, group A offers a disadvantage, and group B has an intermediate effect.